Projeto, construção e avaliação de um dinamômetro para a medição das componentes da força de usinagem no torneamento - Celone, Matteo (2022)
Machining is a manufacturing process that plays an important role in the industry, with the turning operation as one of its protagonists. Thus, it is important to perform studies that helps to understand and, consequently, optimize it. In this context, the knowledge of the machining force components in turning is essential to define the best parameters to increase the productivity and reduce the costs. Thus, the measurement of machining force components using piezoelectric dynamometers has been widely used. However, such devices have a high initial price, which often becomes prohibitive for many research laboratories. In this context, this work presents a proposal of a dynamometer able to measure the components of the machining force in turning using uniaxial load cells based on strain gauge transducers, which are usually cheaper than piezoelectric load cells. The proposed instrument was statically calibrated in a universal testing machine from 0 to 1,5 kN and presented metrological characteristics, such as a linearity of 99.3%, 98.14% and 94.8% in the cutting, feed and radial directions, respectively. Furthermore, the use of a calibration matrix reduced the cross sensitivity from 44% to 3%. Finally, turning tests were performed under different cutting conditions to evaluate the functionality of the instrument, forces up to 252 N, 162 N and 141 N were obtained for cutting, feed and thrust forces, respectively; like previous works.